Media aesthetic component of communication and its manifestation in infographic content - Simakova , Svetlana (Lumina, 2020)
The goal of the present study is to demonstrate the media-aesthetic potential of infographic messages on particular cases. This can be done due to an integrated approach to the analysis of the visual content of media content. That indicates the case study method implementation as well as description and generalization. The theoretical basis of the research is represented by scientific studies of various directions. That includes the history of media and visual media culture; features of the concepts of media culture and media language, media aesthetics; infographics as a tool of media language. The empirical basis of the study is journalistic materials containing infographic content of such publications as by RIA Novosti (ria.ru), TASS (tass.ru). The examples of visual image implementation in the transmission of information — media content containing infographics — are given and analyzed. Considering media aesthetics as the formation of a sensory perception of the proposed media content, the author turns to the philosophical and aesthetic foundations of visual practices in the media and post-humanistic trends in journalism. As a result of the analysis of the theoretical and practical basis of the research, the author comes to the conclusion that today the role of the media aesthetic component of messages is most relevant. And infographics, as the connecting link of language and consciousness, is its most striking tool.